A Rare Manifestation of a Bleeding Tubulovillous Duodenal Polyp Presenting as an Upper Gastrointestinal Hemorrhage - Yaser Khalid; Neethi Dasu; Herman Suga; Michael Itidiare; Richard Walters (Case Reports in Gastroenterology, 2020)
Duodenal polyps have been reported in <1.5% of individuals who undergo esophagogastroduodenoscopy (EGD). We present a case of a 76-year-old male with recurrent hematemesis who was found to have an intestinal-type, pedunculated tubulovillous adenoma in the descending duodenum. An isolated occurrence of nonampullary sporadic duodenal adenoma is a rare finding. Presentation as an upper gastrointestinal hemorrhage is also extremely uncommon. Our patient’s polyp was pedunculated, which is atypical, because most sporadic duodenal adenomas are morphologically flat or sessile. The purpose of this case is to present a rare cause of upper gastrointestinal bleeding and to depict characteristics of an isolated duodenal tubulovillous adenoma and its treatment options.